2017
DOI: 10.1161/circep.116.004471
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Upgrade Versus De Novo Cardiac Resynchronization Therapy on Clinical Response and Long-Term Survival

Abstract: Background— Benefits of cardiac resynchronization therapy (CRT) on morbidity and mortality in selected patients are well known. Although the number of upgrade procedures from single- or dual-chamber devices to CRT is increasing, there are only sparse data on the outcomes of upgrade procedures compared with de novo CRT. This study aimed to evaluate clinical response and survival in patients receiving de novo versus upgrade CRT defibrillator therapy. Methods and Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 22 publications
2
50
0
1
Order By: Relevance
“…Similar results were reported by a few other studies 21,23,24,29,30 with similarly short follow-up periods (ranging from reporting at 290 days to 4 years) or upgrades solely from pacemaker devices. Vamos et al 28 conducted an observational prospective study with an average follow-up of 37 months and reported higher mortality in upgraded patients compared with patients with de novo CRT implants (HR, 1.79; 95% CI, 1.08-2.95; P ¼ 0.023), whereas Cheung et al 20 reported that CRT upgrades were independently associated with increased mortality (adjusted odds ratio, 1.91; 95% CI, 1.67-2.19; P < 0.001) compared with de novo CRT implants. Prior studies have reported similar HF rates between patients with de novo CRT vs CRT upgrades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were reported by a few other studies 21,23,24,29,30 with similarly short follow-up periods (ranging from reporting at 290 days to 4 years) or upgrades solely from pacemaker devices. Vamos et al 28 conducted an observational prospective study with an average follow-up of 37 months and reported higher mortality in upgraded patients compared with patients with de novo CRT implants (HR, 1.79; 95% CI, 1.08-2.95; P ¼ 0.023), whereas Cheung et al 20 reported that CRT upgrades were independently associated with increased mortality (adjusted odds ratio, 1.91; 95% CI, 1.67-2.19; P < 0.001) compared with de novo CRT implants. Prior studies have reported similar HF rates between patients with de novo CRT vs CRT upgrades.…”
Section: Discussionmentioning
confidence: 99%
“…Several analyses have been conducted to date, but thus far, the available evidence has yielded conflicting results. [19][20][21][22][23][24][25][26][27][28][29][30] Bogale et al 19 investigated 692 patients with upgrades to CRT/CRT-D and 1675 patients with de novo CRT/CRT-D, with follow-up of approximately 1 year, and did not find significant differences in survival (P ¼ 0.57) between the 2 groups. Similar results were reported by a few other studies 21,23,24,29,30 with similarly short follow-up periods (ranging from reporting at 290 days to 4 years) or upgrades solely from pacemaker devices.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that survival in patients undergoing a CRT upgrade from chronic RVP was superior to those undergoing de novo CRT implantation with a native LBBB . Gage et al reported on a cohort of 190 paced upgrades to CRT . Over a mean follow up of 4.2 years, the authors reported that patients with paced upgrades had similar survival to patients with de novo implants.…”
Section: Discussionmentioning
confidence: 96%
“…10 Gage et al 10 reported on a cohort of 190 paced upgrades to CRT. 11 Over a mean follow up of 4.2 years, the authors reported that patients with paced upgrades had similar survival to patients with de novo implants. Contrary to these findings, Vamos et al 11 included studies reporting in-hospital outcomes in its analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation